INTERDEPENDENSI ANTARA INSIDER OWNERSHIP, KEPUTUSAN INVESTASI, DAN RISIKO BISNIS - Indri Erkaningrum Florentina (Jurnal Keuangan dan Perbankan, 2013)
Asymmetric information and agency issues made stockholders need to control business activities throughoptimalization insider ownership and investment decision. Optimalization of insider ownership and investmentdecision were expected to make business risk controlled. This research aimed at verifying empirically theinfluencing factors of insider ownership, investment decision, business risk, and finding the interdependencyamong insider ownership, investment decision, and business risk. The samples of this research were 90 realestate and property companies listed at Indonesia Stock Exchange from the year of 2006 to 2010. Simultaneousequation model of three stage least squares (3 SLS) was applied to analyze the interdependency among insiderownership, investment decision, and business risk. The analysis result of interdependency among insiderownership, investment decision, and business risk showed that: there was interdependency between insiderownership and investment; there was interdependency between insider ownership and business risk; investmentinfluenced business risk. The empirical evidence of interdependency among insider ownership, investmentdecision, and business risk helped the companies make financial policies.